Promoting Gender Diversity Research in Slovakia within 7th Framework Programme - Stefankova, J.; Caganova, D.; Moravcik, O. (Elektronika ir Elektrotechnika, 2010)
The article highlights 7th FP project „Improving gender diversity management in materials research institutions“ from the point of view one from 13 project partners and its role in the project, the Faculty of Materials Science and Technology (MTF) STU in Bratislava, Slovakia. The focus is put on the problem of under-representation of women in research and decision making processes and effort to support the institutional culture change for a greater inclusiveness of women scientists in materials research organisations. Finally, the authors would like to exchange and share their Slovak gender issues experience with other colleagues, professionals to contribute for an optimum development of European Research.